 and thus,
ω
1
=
n
2
2
α
[
3
4n
2
+
3A
2
2n
2
].
Thus, the solution for x
1
is given by
x
1
=
B
1
α(1 n
2
)
cos(τ)
B
2
8α
cos(
3τ
n
)
B
3
9α(n
2
1)
cos(3τ)
B
4
α(n 1)(n 3)
cos((1
2
n
)τ)
B
5
α(n + 1)(n + 3)
cos((1 +
2
n
)τ)
B
6
4αn(n 1)
cos((2
1
n
)τ)
B
7
4αn(n + 1)
cos((2 +
1
n
)τ).
The total solution can be written as
ω = n
α + εω
1
,
x(τ) = x
0
+ εx
1
.
293 10.22. For the combination harmonic response, derive Equation 10.80.
Solution:
Solution: Start with
..
x + ω
2
n
x = εβω
2
n
x
3
+ F
1
cos(Ω
1
t) + F
2
cos(Ω
2
t)
Expand x as x(t) = x
0
+ εx
1
, and substitute into the equation of motion to obtain
..
x
0
+ ε
..
x
1
+ ω
2
n
(x
0
+ εx
1
) = εβω
2
n
(x
0
+ εx
1
)
3
+ F
1
cos(Ω
1
t) + F
2
cos(Ω
2
t).
Separating by terms produces
..
x
0
+ ω
2
n
x
0
= F
1
cos(Ω
1
t) + F
2
cos(Ω
2
t)
..
x
1
+ ω
2
n
x
1
= βω
2
n
x
3
0
.
The solution for x
0
is given by
x
0
(t) = G
1
cos(Ω
1
t) + G
2
cos(Ω
2
t).
Substitution of x
0
into the equation for x
1
produces
..
x
1
+ ω
2
n
x
1
= βω
2
n
(G
1
cos(Ω
1
t) + G
2
cos(Ω
2
t))
3
.
Expansion of the cubic term produces
..
x
1
+ ω
2
n
x
1
= βω
2
n
(G
3
1
cos
3
(Ω
1
t) + G
3
2
cos
3
(Ω
2
t) + 3G
1
cos(Ω
1
t)G
2
2
cos
2
(Ω
2
t) + 3G
2
1
cos
2
(Ω
1
t)G
2
cos(Ω
2
t)).
Using the following trigonometric identities given by
(cos(x))
3
=
1
4
(3 cos(x) + cos(3x))
cos
2
(x) cos(y) =
1
4
(cos(y x) + cos(2x + y) + 2 cos(y)),
and simplifying produces
..
x
1
+ ω
2
n
x
1
= C
1
cos(Ω
1
t) + C
2
cos(Ω
2
t)
+C
3
[cos((2Ω
1
+
2
)t) + cos((2Ω
1
2
)t)]
+C
4
[cos((Ω
1
+ 2Ω
2
)t) + cos((Ω
1
2Ω
2
)t)]
+C
6
cos(3Ω
1
t) + C
6
cos(3Ω
2
t),
where
C
1
=
3
4
βω
2
n
G
1
(G
2
1
+ G
2
2
),
C
2
=
3
4
βω
2
n
G
2
(2G
2
1
+ G
2
2
),
C
3
=
3
4
βω
2
n
G
2
1
G
2
,
C
4
=
3
4
βω
2
n
G
1
G
2
2
,
C
5
=
1
4
βω
2
n
G
3
1
,
C
6
=
1
4
βω
2
n
G
3
2
.
294 Section 10.4: The Mathieu Equation
10.23. Derive Equation 10.93.
Solution: For n = 2, we have
θ
0
= cos(2t).
Then,
..
θ
1
+ 4θ
1
= (δ
1
+ 2 cos(2t))θ
0
= (δ
1
+ 2 cos(2t)) cos(2t)
= δ
1
cos(2t) + 2 cos
2
(2t)
= δ
1
cos(2t) + cos(4t) + 1.
For periodicity, δ
1
= 0, and the solution for θ
1
is given by
θ
1
(t) =
1
12
cos(4t)
1
4
.
Substituting this into the equation for θ
2
yields
..
θ
2
+ 4θ
2
= (δ
1
+ 2 cos(2t))θ
1
δ
2
θ
0
= 2 cos(2t)(
1
12
cos(4t)
1
4
) δ
2
cos(2t)
=
1
6
cos(2t) cos(4t) +
1
2
cos(2t) δ
2
cos(2t)
=
1
12
(cos(2t) + cos(6t)) +
1
2
cos(2t) δ
2
cos(2t)
=
1
12
cos(6t) (δ
2
1
2
+
1
12
) cos(2t).
To satisfy periodicity, then δ
2
=
5
12
. Thus,
δ = 4 +
5
12
ε
2
+ ...
295 10.24. Derive Equation 10.94.
Solution: For n=2,
θ
0
= sin(2t).
Then,
..
θ
1
+ 4θ
1
= (δ
1
+ 2 cos(2t))θ
0
,
= (δ
1
+ 2 cos(2t)) sin(2t),
= δ
1
sin(2t) + 2 cos(2t) sin(2t),
= δ
1
sin(2t) + sin(4t).
For periodicity, δ
1
= 0, and the solution for θ
1
is given by
θ
1
(t) =
1
12
sin(4t).
Substituting this into the equation for θ
2
yields
..
θ
2
+ 4θ
2
= (δ
1
+ 2 cos(2t))θ
1
δ
2
θ
0
,
= 2 cos(2t)(
1
12
sin(4t)) δ
2
sin(2t),
=
1
6
cos(2t) sin(4t) δ
2
sin(2t),
=
1
12
sin(2t)
1
12
sin(6t) δ
2
sin(2t).
To satisfy periodicity, then δ
2
=
1
12
. Thus,
δ = 4
1
12
ε
2
+ ...
296 Section 10.5 The van der Pol Equation
10.25. Consider the van der Pol Equation 10.97. Suppose α is a random variable. How do the statistics
of α aﬀect the trajectories shown in Figure 10.14 and the time traces in Figure 10.15.
Solution: Since the curves in both sets of ﬁgures depend on the value of α, uncertainty in that value results
in uncertainties in the curves. One expects that a given variance in α results in a similar variance in the
location of the curves. One can interpret the given curves in Figure 10.11 and the time traces in Figure 10.12
as mean values for a given mean value of α.
297

Get Probabilistic Models for Dynamical Systems, 2nd Edition now with O’Reilly online learning.

O’Reilly members experience live online training, plus books, videos, and digital content from 200+ publishers.